Trends and regional disparities in maternal mortality in China: A nationwide analysis, 2005–2020 - Jue Tang; Fei-Hong Hu (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
This study aimed to explore disparities in MMR across China’s provincial administrative regions from 2005 to 2020. We undertook spatial autocorrelation analysis to quantify the spatial distribution pattern of MMR and conducted Bayesian spatial modeling to explore factors influencing its spatiotemporal differences. The results showed a significant overall decline in MMR during the study period, with reduced regional inequality in its distribution. Spatial autocorrelation analysis confirmed significant positive spatial clustering (global Moran’s I: 0.155–0.367, all P<0.001). Most included variables exerted significant effects on MMR, except the Disease Detection Rate in Women Undergoing Pre-Marital Health Checks. Notably, despite the overall downward trend, persistent geographic disparities existed: MMR was higher in western China and lower in eastern China, with per capita consumer expenditure the most influential factor. This study clarifies the spatiotemporal evolution and key influencing factors of provincial MMR in China, providing insights for targeted interventions to reduce regional disparities.